High-yield fluorescent carbon quantum dot as well as preparation method and application thereof
Through a solvent-free one-step solid phase method, glucose and boric acid are used to synthesize fluorescent carbon quantum dots, solving the problems of high time-consuming, low yield and environmental pollution in the prior art, and achieving efficient and green fluorescent CQDs synthesis.
Patent Information
- Application Number
- CN202411569690.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-04-08
AI Technical Summary
The existing methods for synthesis of carbon quantum dots (CQDs) have problems such as high time-consuming, low yield, multi-solvent use and environmental pollution, making it difficult to achieve green and efficient fluorescent CQDs synthesis.
Using glucose and boric acid as raw materials, fluorescent carbon quantum dots were synthesized under solvent-free conditions by a simple one-step solid phase method. The reaction temperature was 160-200°C and the time was 4-6 hours.
The synthesis of fluorescent carbon quantum dots with high yield (76%) is achieved, which has the advantages of high efficiency, low cost and green environmental protection, and avoids the generation of by-products and solvent contamination.
Smart Images

Figure CN119776003A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to fluorescent carbon nanomaterials, in particular to high-yield fluorescent carbon quantum dots and a preparation method and application thereof. Background Art
[0002] Carbon quantum dots (CQDs) are a new type of 0D carbon-based nanomaterial with unique fluorescence properties, strong photoresponse in the visible light region and high conductivity, low cytotoxicity, excellent biocompatibility, good hydrophilicity and easy surface modification. They have shown great application prospects in biological imaging, anti-counterfeiting printing, fluorescence sensing, biomedicine, optoelectronic devices, energy conversion and storage.
[0003] The existing synthesis methods of CQDs are generally divided into top-down and bottom-up strategies. The CQDs obtained by the top-down method have low quantum yield and poor water solubility, and need to be modified to improve their optical properties; the bottom-up method is a common method used by researchers to synthesize CQDs, which uses polymerizable functional groups in precursor molecules to create larger carbon-based structures. Among the currently reported CQDs synthesis methods, both top-down and bottom-up methods need to be synthesized in liquid phase, which has the following disadvantages: 1) The reaction takes about 12-24 hours, the separation and purification time is generally 2-3 days, and the drying takes about 1 day, which is time-consuming and inefficient; 2) During the reaction stage, the solvent usually participates in the reaction to form a large number of by-products, making the separation and purification process of CQDs cumbersome, and the actual yield of the CQDs finally obtained is low, generally 30%, or even lower; 3) In the synthesis and purification stage, a large amount of organic solvents are needed, which not only increases the preparation cost, but also produces a large amount of difficult-to-treat waste liquid, causing potential environmental pollution risks. Therefore, developing a green and efficient method to synthesize fluorescent CQDs still faces great challenges.
[0004] In addition, polymer hydrogels have broad application prospects in many fields such as biomedical devices, fluorescent anti-counterfeiting printing and wearable electronics. However, polymer hydrogels currently have insufficient comprehensive performance such as optics, mechanics and biocompatibility, and their processing and manufacturing technology mainly relies on casting, mold shaping, injection molding and other methods, facing technical problems such as pattern processing and device integration difficulties, which limits its practical application of customization and 3D fluorescent printing and product commercialization prospects. CQDs contain a large number of functional groups such as carboxyl, amino and hydroxyl groups on the surface. This structural feature not only makes CQDs highly water-soluble, but also makes it an ideal component for constructing hydrogels. Therefore, it is expected that CQDs can be introduced into polymer hydrogels to give hydrogels more properties, such as fluorescence, stimulus response, self-healing, good mechanical strength and biological functions. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-yield fluorescent carbon quantum dots and a preparation method and application thereof. The fluorescent carbon quantum dots are synthesized by a simple one-step solid-phase method, which has the advantages of high yield, high efficiency, low cost and green environmental protection.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing high-yield fluorescent carbon quantum dots comprises the following steps:
[0008] Step 1, mix 1.0-1.6 mmol of glucose and 0.4-1.0 mmol of boric acid, with a total of 2 mmol of glucose and boric acid, and grind evenly to obtain a mixture A;
[0009] Step 2: Place the polytetrafluoroethylene container containing the mixture A in an oven and heat it at 160-200° C. for 4-6 hours. After the reaction is completed, cool it naturally to room temperature and grind it to obtain brown-yellow powdered carbon quantum dots.
[0010] Furthermore, the yield of the carbon quantum dots is 76%.
[0011] A type of carbon quantum dot, with a fluorescence quantum yield of 4.5% in the solid state.
[0012] A hydrogel fluorescent ink containing carbon quantum dots is prepared by the following method:
[0013] S1. Dissolve 2-3 g of polyvinyl alcohol in 20-30 mL of polyacrylic acid to obtain solution B;
[0014] S2. Add 0.4-1 g of powdered carbon quantum dots into solution B, stir magnetically for 90 min at 90° C., then cool to room temperature, and centrifuge at high speed to obtain a uniform hydrogel fluorescent ink containing carbon quantum dots.
[0015] Furthermore, the centrifugal speed of the high-speed centrifugation in step S2 is 6000-9000 r / min, and the time is 5 min.
[0016] The hydrogel fluorescent ink is used as a fluorescent anti-counterfeiting ink in the field of 3D printing.
[0017] Compared with the prior art, the present invention has the following technical effects:
[0018] The present invention uses glucose and boric acid as raw materials, and synthesizes powdered fluorescent carbon quantum dots (CQDs) by a simple one-step solid phase method, which has the following advantages: 1) The reaction process does not require any solvent, which reduces the generation of by-products, thereby simplifying the post-processing steps, not only the preparation method, but also the limitation and improvement of the synthesis efficiency, and can effectively prevent the problem of low CQDs yield caused by the cumbersome post-processing process, so that the CQDs yield reaches 76.0%, which is much higher than the yield of CQDs synthesized by the existing liquid phase method; 2) It prevents the secondary pollution problem caused by organic solvents, which is more green and environmentally friendly; 3) It does not require a high-pressure reactor, reducing safety hazards. In short, the method for synthesizing CQDs of the present invention has the significant advantages of being simple, green, safe, efficient and low-cost, and provides an effective strategy for the large-scale production of fluorescent CQDs.
[0019] The fluorescence quantum yield of the CQDs synthesized by the present invention in water is 15.9%, and in particular, the fluorescence quantum yield of the solid-state CQDs can still reach 4.5%, thereby avoiding the fluorescence quenching phenomenon of the existing CQDs under solid-state conditions.
[0020] The surface of the CQDs synthesized in the present invention has abundant oxygen-containing groups, which give the CQDs good hydrophilicity and fluorescence properties. The CQDs are applied to hydrogel ink to obtain 3D printing fluorescent anti-counterfeiting ink for printing encrypted information, which is convenient for printing different anti-counterfeiting patterns. The CQDs show high dimensional accuracy and fluorescence color rendering ability, giving the 3D printed products excellent anti-counterfeiting properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 : TEM image of powdered CQDs prepared in Example 3 of the present invention;
[0022] Figure 2 : XPS spectrum of powdered CQDs prepared in Example 3 of the present invention;
[0023] Figure 3 : Excitation spectra and fluorescence emission spectra of CQDs aqueous solutions prepared in Examples 1 to 4 of the present invention;
[0024] Figure 4 : Appearance photos of the CQDs aqueous solution prepared in Example 3 of the present invention under sunlight and ultraviolet light;
[0025] Figure 5 : Excitation spectrum and fluorescence emission spectrum of powdered CQDs prepared in Example 3 of the present invention;
[0026] Figure 6 : Photos of the appearance of powdered CQDs prepared in Example 3 of the present invention under sunlight and ultraviolet light;
[0027] Figure 7 : The hydrogel ink prepared in Example 3 of the present invention is used as a 3D printing fluorescent anti-counterfeiting ink to print different patterns on a PET substrate. DETAILED DESCRIPTION
[0028] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0029] Example 1
[0030] Step 1: Preparation of carbon quantum dots
[0031] Step 1.1, mix 1 mmoL of glucose and 1 mmoL of boric acid, grind evenly, and obtain a mixture A;
[0032] Step 1.2, transfer mixture A into a 100 mL tetrafluoroethylene container, place it in an oven, heat it at 160°C for 6 h, and after the reaction is completed, naturally cool it to room temperature and grind it to obtain brown-yellow powdered carbon quantum dots CQDs;
[0033] Step 1.3, add 50 mL of ultrapure water to each glass beaker containing 50 mg of brown-yellow powdered CQDs, and ultrasonically disperse for 30 min to obtain a transparent yellow-brown CQDs aqueous solution;
[0034] Step 2: Preparation of hydrogel fluorescent ink containing CQDs
[0035] Step 2.1, dissolving 2 g of polyvinyl alcohol in 20 mL of polyacrylic acid to obtain solution B;
[0036] Step 2.2, add 0.4 g of the powdered CQDs prepared in step 1 to solution B, stir magnetically at 90°C for 90 min, then cool to room temperature, and then centrifuge at a high speed of 6000 r / min for 5 min to obtain a uniform hydrogel fluorescent ink containing CQDs.
[0037] Example 2
[0038] Step 1: Preparation of carbon quantum dots
[0039] Step 1.1, 1.2 mmoL of glucose and 0.8 mmoL of boric acid were mixed and ground evenly to obtain a mixture A;
[0040] Step 1.2, transfer mixture A into a 100 mL tetrafluoroethylene container, place it in an oven, heat it at 180°C for 5 h, and after the reaction is completed, naturally cool it to room temperature and grind it to obtain brown-yellow powdered carbon quantum dots CQDs;
[0041] Step 1.3, add 50 mL of ultrapure water to each glass beaker containing 50 mg of brown-yellow powdered CQDs, and ultrasonically disperse for 30 min to obtain a transparent yellow-brown CQDs aqueous solution;
[0042] Step 2: Preparation of hydrogel fluorescent ink containing CQDs
[0043] Step 2.1, dissolving 2 g of polyvinyl alcohol in 20 mL of polyacrylic acid to obtain solution B;
[0044] Step 2.2, add 0.6 g of the powdered CQDs prepared in step 1 to solution B, stir magnetically at 90°C for 90 min, cool to room temperature, and then centrifuge at a high speed of 7000 r / min for 5 min to obtain a uniform hydrogel fluorescent ink containing CQDs.
[0045] Example 3
[0046] Step 1: Preparation of carbon quantum dots
[0047] Step 1.1, 1.4 mmoL of glucose and 0.6 mmoL of boric acid were mixed and ground evenly to obtain a mixture A;
[0048] Step 1.2, transfer mixture A into a 100 mL tetrafluoroethylene container, place it in an oven, heat it at 200°C for 4 h, and after the reaction is completed, naturally cool it to room temperature and grind it to obtain brown-yellow powdered carbon quantum dots CQDs;
[0049] Step 1.3, add 50 mL of ultrapure water to each glass beaker containing 50 mg of brown-yellow powdered CQDs, and ultrasonically disperse for 30 min to obtain a transparent yellow-brown CQDs aqueous solution;
[0050] Step 2: Preparation of hydrogel fluorescent ink containing CQDs
[0051] Step 2.1, dissolving 2 g of polyvinyl alcohol in 20 mL of polyacrylic acid to obtain solution B;
[0052] Step 2.2, add 0.8 g of the powdered CQDs prepared in step 1 to solution B, stir magnetically at 90°C for 90 min, then cool to room temperature, and then centrifuge at a high speed of 8000 r / min for 5 min to obtain a uniform hydrogel fluorescent ink containing CQDs.
[0053] Steps 1.1 to 1.2 of Example 3 were repeated three times, and the powdered carbon quantum dots CQDs were collected respectively. The yield of the carbon quantum dots CQDs prepared each time was calculated, and the average value was calculated to obtain a yield of CQDs powder of 76.0%.
[0054] Example 4
[0055] Step 1: Preparation of carbon quantum dots
[0056] Step 1.1, 1.6 mmoL of glucose and 0.4 mmoL of boric acid were mixed and ground evenly to obtain a mixture A;
[0057] Step 1.2, transfer mixture A into a 100 mL tetrafluoroethylene container, place it in an oven, heat it at 200°C for 4 h, and after the reaction is completed, naturally cool it to room temperature and grind it to obtain brown-yellow powdered carbon quantum dots CQDs;
[0058] Step 1.3, add 50 mL of ultrapure water to each glass beaker containing 50 mg of brown-yellow powdered CQDs, and ultrasonically disperse for 30 min to obtain a transparent yellow-brown CQDs aqueous solution;
[0059] Step 2: Preparation of hydrogel fluorescent ink containing CQDs
[0060] Step 2.1, dissolving 2.5 g of polyvinyl alcohol in 25 mL of polyacrylic acid to obtain solution B;
[0061] Step 2.2, add 1 g of the powdered CQDs prepared in step 1 to solution B, stir magnetically at 90°C for 90 min, then cool to room temperature, and then centrifuge at a high speed of 9000 r / min for 5 min to obtain a uniform hydrogel fluorescent ink containing CQDs.
[0062] Example 5
[0063] Step 1: Preparation of carbon quantum dots
[0064] Step 1.1, 1.3 mmoL of glucose and 0.7 mmoL of boric acid were mixed and ground evenly to obtain a mixture A;
[0065] Step 1.2, transfer mixture A into a 100 mL tetrafluoroethylene container, place it in an oven, heat it at 180°C for 4 h, and after the reaction is completed, naturally cool it to room temperature and grind it to obtain brown-yellow powdered carbon quantum dots CQDs;
[0066] Step 1.3, add 50 mL of ultrapure water to each glass beaker containing 50 mg of brown-yellow powdered CQDs, and ultrasonically disperse for 30 min to obtain a transparent yellow-brown CQDs aqueous solution;
[0067] Step 2: Preparation of hydrogel fluorescent ink containing CQDs
[0068] Step 2.1, dissolving 3 g of polyvinyl alcohol in 30 mL of polyacrylic acid to obtain solution B;
[0069] Step 2.2, add 0.7 g of the powdered CQDs prepared in step 1 to solution B, stir magnetically at 90°C for 90 min, then cool to room temperature, and then centrifuge at a centrifugal rate of 6500 r / min for 5 min to obtain a uniform hydrogel fluorescent ink containing CQDs.
[0070] from Figure 1 It can be seen that the powdered CQDs prepared in Example 3 are spherical, and the particles are completely dispersed without any agglomeration. The particle size of the CQDs is about 5.0 nm.
[0071] Figure 2 This is the XPS energy spectrum of the powdered CQDs prepared in Example 3, where: (a) is the XPS full spectrum, (b) is the O1s fine spectrum, (c) is the B1s fine spectrum, and (d) is the C1s fine spectrum. It can be seen that the CQDs prepared in Example 3 are mainly composed of elements such as C, O, and B, and the contents of C, O, and B are 46.5%, 40.4%, and 13.1%, respectively. The C element mainly exists in the form of CO, C=O, BC, and CC / C=C bonds, the O element mainly exists in the form of CO, C=O, BO, and OH bonds, and the B element mainly exists in the form of BO and BCO2. From the XPS analysis, it can be concluded that the surface of CQDs contains abundant organic groups, so that CQDs have good hydrophilicity and fluorescence properties.
[0072] The excitation spectra and fluorescence emission spectra of the CQDs aqueous solutions prepared in Examples 1 to 4 are as follows: Figure 3 As shown, it can be seen that the CQDs aqueous solutions prepared in Examples 1 to 4 all have good fluorescence properties, wherein the best excitation spectrum is located at around 350 nm, and the corresponding best fluorescence emission spectrum is located in the blue light region at around 450 nm.
[0073] The CQDs aqueous solution prepared in Example 3 was placed under sunlight and ultraviolet light for observation. The results are as follows: Figure 4 As shown in the figure, the CQDs aqueous solution appears transparent brown-yellow under sunlight and emits bright blue fluorescence under 365nm ultraviolet light, which is consistent with Figure 3 The fluorescence spectrum of CQDs is consistent with that of the original. At the same time, the fluorescence quantum yield of CQDs aqueous solution was measured by absolute method to be 15.9%.
[0074] from Figure 5 It can be seen that the optimal excitation spectrum of the powdered CQDs prepared in Example 3 is at 460 nm, and the corresponding optimal fluorescence emission spectrum is at 550 nm, which indicates that the synthesized CQDs have good fluorescence in the solid state.
[0075] from Figure 6It can be seen that the powdered CQDs prepared in Example 3 appear light brown in sunlight and emit bright green fluorescence under 365nm ultraviolet light. Figure 5 The fluorescence spectrum of the CQDs powder prepared in Example 3 was measured by absolute method, and the fluorescence quantum yield was 4.5%.
[0076] The hydrogel fluorescent ink containing CQDs prepared in Example 3 was loaded into a 3D printer, and the following can be printed on a PET substrate: Figure 7 The different complex patterns shown, among which Figure 7 (a) is a small fish, Figure 7 (b) is a bow tie. After drying in sunlight, the fish and bow tie are almost invisible on the PET substrate. However, under 254nm and 365nm ultraviolet light, it shows a clear blue-green pattern, indicating that the CQDs hydrogel fluorescent ink prepared in Example 3 can be used as a fluorescent anti-counterfeiting ink for printing encrypted information, thereby improving the anti-counterfeiting performance of 3D printed products.
Claims
1. A method for preparing high-yield fluorescent carbon quantum dots, characterized in that: The steps include: Step 1, mix 1.0-1.6 mmol of glucose and 0.4-1.0 mmol of boric acid, with a total of 2 mmol of glucose and boric acid, and grind evenly to obtain a mixture A; Step 2: Place the polytetrafluoroethylene container containing the mixture A in an oven and heat it at 160-200° C. for 4-6 hours. After the reaction is completed, cool it naturally to room temperature and grind it to obtain brown-yellow powdered carbon quantum dots.
2. The method for preparing high-yield fluorescent carbon quantum dots according to claim 1, characterized in that: The yield of the carbon quantum dots was 76%.
3. A carbon quantum dot synthesized based on the preparation method of high-yield fluorescent carbon quantum dots according to claim 1 or 2, characterized in that: In solid state, the fluorescence quantum yield is 4.5%.
4. A hydrogel fluorescent ink, characterized in that: Contains the carbon quantum dots as claimed in claim 3.
5. The hydrogel fluorescent ink according to claim 4, characterized in that: Prepared by the following method: S1. Dissolve 2-3 g of polyvinyl alcohol in 20-30 mL of polyacrylic acid to obtain solution B; S2. Add 0.4-1 g of powdered carbon quantum dots into solution B, stir magnetically for 90 min at 90° C., then cool to room temperature, and centrifuge at high speed to obtain a uniform hydrogel fluorescent ink containing carbon quantum dots.
6. The hydrogel fluorescent ink according to claim 5, characterized in that: The centrifugal speed of the high-speed centrifugation in step S2 is 6000-9000 r / min, and the time is 5 min.
7. Use of the hydrogel fluorescent ink according to any one of claims 4 to 6 as a fluorescent anti-counterfeiting ink in the field of 3D printing.